Improvements in skin quality parameters in postmenopausal participants after use of topical growth factor serum. (12th November 2022) - Gold, Michael H.; Wilson, April; Makino, Elizabeth; Mehta, Rahul
Abstract: Background: Photodamage can induce skin aging processes that can be particularly concerning for postmenopausal women. Growth factors from hypoxic human fibroblast‐conditioned media have demonstrated improvements in skin quality parameters. Aims: The aim of the study was to assess efficacy and tolerability of topical combination‐treatment hypoxic growth factor serum (TNS A+) in postmenopausal women with moderate to severe facial photodamage. Patients/Methods: In this 12‐week, open‐label, single‐center study, participants used TNS A+ serum twice daily. Postmenopausal women (40–65 years of age) with Fitzpatrick skin types I–VI and modified Griffiths scale scores 4–9 were eligible. Clinical and participant‐reported assessments were evaluated at Weeks 6 and 12. Statistical significance was defined as p ≤ 0.05. Results: There were 17 enrolled participants. TNS A+ treatment demonstrated significant improvements from baseline in fine lines and wrinkles in periocular, forehead, and cheek areas at Week 12 and the perioral area at Weeks 6 and 12. Significant improvements from baseline in coarse lines and wrinkles were observed for the perioral area at Week 12 and periocular and cheek areas at Weeks 6 and 12. Improvements in overall photodamage, skin tone evenness, and tactile roughness were significantly greater at Weeks 6 and 12 versus baseline. Most participants reported TNS A+ made their skin look and feel smooth, soft, and rejuvenated; improved skin radiance; made lines and wrinkles less apparent; and improved skin texture. No treatment‐related adverse events were reported. Conclusions: The TNS A+ regimen was well tolerated and provided significant improvements in skin quality in postmenopausal women with moderate to severe facial photodamage.